New and versatile routes to zirconium imido dichloride compounds. - Dubberley, SR; Evans, S; Boyd, C; Mountford, P (2005)
Reactions of zirconium dialkyl- or bis(amido)-dichloride complexes "[Zr(CH2SiMe3)2Cl2(Et2O)2]" or [Zr(NMe2)2Cl2(THF)2] with primary alkyl and aryl amines are described. Reaction of "[Zr(CH2SiMe3)2Cl2(Et2O)2]" with RNH2 in THF afforded dimeric [Zr2(mu-NR)2Cl4(THF)4](R=2,6-C6H3iPr2 (1), 2,6-C6H3Me2 (2) or Ph (3)), [Zr2(mu-NR)2Cl4(THF)3](R=tBu (5), iPr (6), CH2Ph (7)), or the "ate" complex [Zr2(mu-NC6F5)2Cl6(THF)2{Li(THF)3}2](4, the LiCl coming from the in situ prepared "[Zr(CH2SiMe3)2Cl2(Et2O)2]"). With [Zr(NMe2)2Cl2(THF)2] the compounds [Zr2(mu-NR)2Cl4(L)x(L')y](R=2,6-C6H3iPr2 (8), 2,6-C6H3Me2 (9), Ph (10) or C6F5 (11); (L)x(L')y=(NHMe2)3(THF), (NHMe2)2(THF)2 or undefined), [Zr2(mu-NtBu)2Cl4(NHMe2)3] (12) and insoluble [Zr(NR)Cl2(NHMe2)]x(R=iPr (13) or CH2Ph (14)) were obtained. Attempts to form monomeric terminal imido compounds by reaction of or with an excess of pyridine led, respectively, to the corresponding dimeric adducts [Zr2(mu-2,6-C6H3Me2)2Cl4(py)4] (15) and [Zr2(mu-NtBu)2Cl4(py)3] (16). The X-ray structures of 1, 2, 4, 8, 12 and 15 have been determined.